Comparison Analysis of Service Performance Using Kruskal Wallis-Friedman Test to Minimize Waiting Time in Toll Gate System - Sri Wahyuningsih, Suluh; Herli Sumerli A, Chevy; Fajri, T. Irfan; Octiva, Cut Susan; Adhicandra, Iwan (Jurnal Informasi dan Teknologi, 2023)
The purpose of this study is to compare how well conventional, automatic, and OBU toll gates perform in terms of service. The author of this study employed two data collection techniques: primary data was gathered through interviews and field observations, and secondary data was obtained through a review of the literature. You choose which features and parameters are subject to change while the simulation is running. The system will be used to simulate how each algorithm performs in accordance with ideas and scenarios that have already been decided. Following the recording of the simulation findings, the verification step will be completed. On the basis of the outcomes of earlier data processing and analysis, the following conclusions are possible: In creating a toll gate model, two automatic toll booths spaced 60 meters apart from the toll gate were used as simulations to approximate the real thing. utilizing the Kruskal-Wallis-Friedman test computations to compare the performance of the toll gate service with six scenarios. The OBU-OBU scenario has the system's shortest waiting time, according to the computation findings. Conversely, the server utilities that are in use are traditional and traditional.